PHYTOSOCIOLOGY OF MAI DHANI HILL NEAR MuzAFFARABAD, AZAD KASHMIR II.WINTER VEGETATION (Biological Sciences - PJSIR, 2002)
Six plant communities viz., Themeda-Dodonaea-Maytenus, Dodonaea-Maytenus, Phoenix- Cyn odon-i\1icromeria, Dodonaea-Otostegia-Themeda, Dodonaea-Th emeda-Mallotus, Pinus-Hypod ematium-Dodonaea were established on the basis of phytosociological attributes on sunside at Mai Dhani Hill, Muzaffarabad in December , 1995. The highest species diversity is shown by Phoenix-Cynodon-Micromeria communi ty at 970 m elevation while the lowest species diversity i s shown by Dodonaea-Otostegia-Themeda community at 980 m elevation. With the increase of  an  altitude  the species diversity  decreased. The  study  area has sandy loam  to loam  type soil.  The pH  of the soil  in  the study  area  was slightlyalkaline  in  nature. Organic matter  varies from  2 .0 to 2.65%. The  CaC0   content varies from  1 5.7 to 23.2% while  total3soluble  salts vary  from  0.022  to 0.58%. There   was a  decrease in  soil temperatu re from  lower to higher altitudes.